Perlindungan Hukum Pekerja Terhadap Perjanjian Kerja - Siahaan, Zefany Odelia Cristy; Tjoanda, Merry; Pattipawae, Dezonda Rosiana (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Labor law guarantees that every worker has the right to a decent livelihood for humanity, one of which is realized in the form of wages and employers are prohibited from paying wages under the minimum wage provisions. This emphasizes the provision of legal protections for workers to ensure the fulfillment of workers' basic rights. However, in practice there are stillemployers who provide workers with wages below the minimum wage.  Sothat workers have difficulty meeting their needs and workers' right to a decent livelihood for humanity is not achieved. Purposes of the Research: to find out and analyze the implementation of the employment agreement and the legal protection of workers against the employment agreement. Methods of the Research: This research uses the normative legal research method which is carried out by examining legal materials to answer the legal issues faced.Results of the Research: The results showed   that the implementation of the   employment agreement had met the requirements of the employment agreement, but the entrepreneur CV Gemilang Sukses defaulted on the wage element.    Because, in the employment agreement, CV Gemilang Sukses employers promised to pay workers' wages according to the Ambon City Minimum Wage. However, in its implementation, it turns out that the entrepreneur CV Gemilang Sukses pays workers' wages below the Ambon City Minimum Wage.  Then, the legal protection that workers can get from employment agreements is in the form of legal protection of workers for wages, work time, rest time and time off from working overtime, disabled workers, female workers, pregnant, childbirth, child labor, occupational safety and health, termination of employment, labor social security and morals, decency and treatment according to human dignity and dignity. . Such protection can be provided through preventive legal protections such as the creation of employment agreements and the filing of objections before signing employment agreements and through the protection of repressive laws, namely the establishment of efforts to resolve labor disputes.  The existence of legal protection in order to ensure the fulfillment  of the basic rights of workers, equalityvtreatment without discrimination for the realization of welfare for workers   and their families, taking into account the progress of the business world and the interests of employers.